Secretory spaces in species of the clade Dipterygeae (Leguminosae, Papilionoideae) - Palermo,Fernanda Helena (2017)
ABSTRACT Dipteryx, Pterodon and Taralea are legume genera known for secreting oils, produced in secretory canals and cavities, with medicinal properties. We analyzed the distribution, morphology and histochemistry of these glands in leaves and stems of Dipteryx alata, Pterodon pubescens and Taralea oppositifolia, three Neotropical species, using standard techniques for anatomy and histochemistry. Secretory spaces, i.e. secretory cavities and canals, exhibited a wide lumen and a single layer of epithelium. Digitiform epithelial cells, forming trabeculae protruding into the lumen, were seen in all three species. Secretory cavities with a rounded or oval lumen and secretory canals with an elongated lumen in longitudinal sections were found only in T. oppositifolia. In D. alata and P. pubescens, only secretory cavities were found. In P. pubescens, secretory cavities occurred in the leaf blade margin. In T. oppositifolia, secretory spaces were much more numerous than in the other two species. Terpenes, total lipids, phenolic compounds, alkaloids and polysaccharides were detected in the secretory spaces of the three species. The abundance of secretory spaces, the presence of canals in T. oppositifolia and the position of cavities in P. pubescens are features with potential diagnostic value for their respective genera.